GPR37 promotes cancer growth by binding to CDK6 and represents a new theranostic target in lung adenocarcinoma. (September 2022) - Xie, Xiaona; Cai, Xueding; Zhou, Feng; Li, Yaozhe; Liu, Qianzi; Cai, Luqiong; Zhu, Wenjing; Wei, Jinqiu; Jin, Chenying; Liu, Zitian; Jiang, Chunhui; Zhao, Haiyang; et al.
Abstract: Lung adenocarcinoma (LUAD) is associated with poor prognosis. Identifying novel cancer targets and helpful therapeutic strategies remains a serious clinical challenge. This study detected differentially expressed genes in The Cancer Genome Atlas (TCGA) LUAD data collection. We also identified a predictive DNA biomarker, G protein-coupled receptor 37 (GPR37), which was verified as a prognostic biomarker with a critical role in tumor progression. In human LUAD specimens and microarray analyses, we determined that GPR37 was significantly upregulated and associated with a poor prognosis. GPR37 downregulation markedly inhibited the proliferation and migration of LUAD both in vitro and in vivo . Mechanistically, GPR37 could bind to CDK6, thereby facilitating tumor progression in LUAD by inducing cell cycle arrest at the G1 phase. GPR37 also facilitates tumorigenesis in xenograft tumors in vivo . High-throughput screening for GPR37-targeted drugs was performed using the Natural Products Library, which revealed the potential of Hypocrellin B to inhibit GPR37 and cell growth in LUAD. We demonstrated that Hypocrellin B suppressed LUAD cell proliferation and migration both in vitro and in vivo via GPR37 inhibition. Collectively, our findings reveal the role of GPR37 in LUAD progression and migration and the potential of GPR37 as a target for the treatment of LUAD. Thus, the specific inhibition of GPR37 by the natural product Hypocrellin B may possess the potential for the treatment of LUAD. Graphical Abstract: ga1